Mental Health and the Intersection of Perceived Discrimination and Social Inequalities Among Students in Germany – a Quantitative Intersectional Study - Laura Pilz González; Enrique Alonso-Perez; Enrique Alonso-Perez; Jennifer Lehnchen; Zita Deptolla; Eileen Heumann; Hürrem Tezcan-Güntekin; Katherina Heinrichs; Christiane Stock; Christiane Stock (International Journal of Public Health)
ObjectivesDiscrimination poses a threat to the mental health of university students, especially those affected by social inequality, yet understanding its intersectional impact remains limited. This study examines the intersection of social inequalities with perceived discrimination to explore differences in mental health among students in Germany.MethodsData from the cross-sectional project “Survey on study conditions and mental health of university students” (n = 14,592) were analysed using Multilevel Analysis of Individual Heterogeneity and Discriminatory Accuracy (MAIHDA). Depressive symptoms, cognitive stress symptoms, and exhaustion were examined across 48 intersectional strata based on gender, first academic generation, family care tasks, and perceived discrimination.ResultsThe MAIHDA analysis revealed substantial between strata variance, with most of it explained by additive rather than intersectional interaction effects. Perceived discrimination, diverse or female gender, first academic generation, and family care tasks (for exhaustion only) were associated with worse mental health outcomes.ConclusionThe profound associations between perceived discrimination and the mental health among university students call for urgent attention and intervention within university settings. Adopting an intersectional lens is key to identifying and addressing inequalities.